Roles of mitochondria in cancer targeting therapeutics. - Sim, Kae Hwan. (2011)
Dysfunctions of mitochondria have been implicated as the important factor of a wide variety of diseases. Significantly, mitochondrion has emerged as the potential targets for cancer targeting therapeutics. In particular, recent findings show that reversible protein phosphorylation, which is a crucial but largely overlooked means of mitochondrial post translational modification, regulates the mitochondrial functions in the oncogenic signaling network. Comprehensive understanding of mitochondrial phosphoproteomics will thus help in breakthrough of cancer therapy. Nonetheless the substoichiometric level of protein phosphorylation largely hinders the global analysis of mitochondrial phosphoproteome. Here we report optimization of several phosphopeptide enrichment approaches including batchwise IMAC, TiO2, ERLIC, SCX and ERLIC chromatography for efficient identification of phosphopeptides and phosphoproteins. A novel combinatorial enrichment strategy that couples SDS-PAGE to batchwise ERLIC, IMAC and TiO2 sequentially has been developed to enrich for phosphopeptides of SNU1 and SNU5 cancer cells mitochondria. Finally we identified 403 and 356 phosphoproteins in SNU1 and SNU5 mitochondria respectively. A list of 44 important phosphoproteins is summarized. These results revealed diverse crucial phosphorylation activities involved in the regulation of mitochondrial functions in cancer cells.